Management of SMEs in Mexico. In the face of new business scenarios and the theory of the agency - López Mejía, María Rosa; Gómez Martínez, Alicia; Sánchez Meléndez, Mitzi Donaji (Estudios de Administración, 2020)
This century is already characterized by seriously competitive business environment. For this reason, the purpose of this work was to identify the use of basic management tools such as mission and vision, organizational charts and planning as well as accounting systems and internal control in SMEs in Puebla, Mexico, according to their size, age and profile according to the director of the Agency Theory. It is an empirical, quantitative and cross-sectional study whose results show that family SMEs run by the director and the son of mature companies predominate the corporate structure and are the ones that take most advantage of management tools but that their use should be boosted throughout businesses in México.